Adaptive control of a position servo as a first stage in fatigue investigation - Mohd Noor, Samsul Bahari; Alwi, Erny Aznida (Universiti Putra Malaysia Press, 2002)
An aircraft will encounter various forces and pressures applied by the air to its structure during flight. Therefore static and dynamic fatigue testing are necessary to make sure its structure can stand various force pattern imposed on it. In this study, a dc servo was configured for position control. Hence, with some modification it can then be used for applying force patterns to a cantilever beam, which represent a wing of an airplane. An adaptive controller has been designed to have a good tracking to the changes in set point, to generate control signal that is far from saturation and to minimize the effect of force interaction when two channel actuators are used. The use of adaptive control scheme on the dc servo can overcome the problems of uncertainty and variation in parameter estimation.